Significant improvements in the olfactory sensitivity of bipolar I disorder patients during euthymia versus manic episodes: a longitudinal study - Liu, Xianlin; Su, Langjun; Li, Yingying; Yuan, Huiqian; Zhao, Ao; Yang, Chunhong; Chen, Chao; Li, Chunyang (Frontiers in Psychiatry, 2024)
Introduction: Research has indicated that individuals diagnosed with bipolar disorder (BD) might experience alterations in their olfaction or levels of serum tumor necrosis factor-α (TNF-α), but no studies have investigated olfactory function and serum TNF-α in BD patients simultaneously. Moreover, there is a lack of existing research that compares the longitudinal olfactory function between individuals with manic and euthymic BD I. Methods: Patients with manic BD I (BDM, n=44) and healthy controls (HCs, n=32) were evaluated symptoms (measured via the Young Manic Rating Scale, YRMS), social function (measured via the Global Assessment Function, GAF), serum TNF-α, and olfactory function (via the Sniffin' Sticks test) including olfactory sensitivity (OS)and olfactory identification (OI). The BDM patients were followed up to the remission period and re-evaluated again. We compared OS, OI and serum TNF-α in manic and euthymic patients with BD I and HCs. We examined the correlation between olfactory function and symptoms, social function, and serum TNF-α in patients with BD I.The BDM patients exhibited significantly lower OS and OI compared to the HCs (Z = -2.235, P = 0.025; t = -6.005, P < 0.001), while a positive correlation was observed between OS and GAF score (r = 0.313, P = 0.039). The OS in the BD I remission group (n=25) exhibited significantly superior performance compared to the BDM group (t = -4.056, P < 0.001), and the same as that in the HCs (P = 0.503). The change in OS showed a positive correlation with the decrease in YMRS score (r = 0.445, P = 0.026), and a negative correlation with the course of disease (r = -0.594, P = 0.002). The TNF-α in BD I patients was significantly lower compared to HCs (P < 0.001), and not significantly correlated with olfactory function (all P > 0.05).The findings suggest that OS and OI are impaired in BDM patients, and the impaired OS in those patients can be recovered in the remission stage. OI may serve as a potential characteristic marker of BD. OS might be useful as an index for BDM treatment efficacy and prognosis.